ANALISA MOTIVASI WISATA BELANJA PADA FACTORY OUTLETDI KOTA BANDUNG - Octavia, Damayanti; Aulia Utami, Sinta (IKONOMIKA, 2016)
Abstract - The existence of potential of Bandung as the city’s services have made the city of Bandung, the award winning “tourism award 2011 as the most favorite city and the best service quality city”. Bandung try to become city services in the fields of fashion, food, and the arts. Even the fashion industry became one of the leading industrial sectors developed by the city of Bandung as the originator of the establishment of the factory outlet. The method used in this research is quantitative and descriptive. The studied samples were processed by non-probability method namely purposive sampling with the total sampling of 400 respondents. Data analysis techniques used was cross tabulation and chi-square.The conclusions of this research are there is a different between the shopping tourist and the tourist shopper, while the shopping tourist have hedonic shopping motivation higher.